Invasive aspergillosis in a tertiary-care hospital in Thailand - Sasisopin Kiertiburanakul (2018)
Background: Invasive aspergillosis (IA) is one of the most common and serious fungal infections in immunocompromised host. Available data regarding IA among Asian patients are limited. Objective: To determine patients' characteristics, clinical presentation, treatment, and outcomes of patients with IA in a Tertiary-care Hospital in Thailand. Material and Method: The authors retrospectively reviewed medical and laboratory records of adult patients with IA from January 2000 to December 2005. Results: Ninety-four patients were identified and classified as proven (n = 35), probable (n = 10), and possible IA (n = 49) according to the criteria designed for cancer patients (EORTC/MSG). Mean ± SD age was 48 ± 19 (range, 17-89) years old and 54 patients (57%) were male. Acute leukemia was the most common underlying condition (30%). Major predisposing factors were neutropenia (39%), chemotherapy (34%), and receiving corticosteroid therapy (25%). Common sites of infection were lungs (68%), sinus (17%), and eyes (8%). Aspergillus fumigatus (67%) was the most frequently isolated species. Amphotericin B followed by itraconazole was the mainstay of treatment. Thirty-six patients (38%) had complete or partial response to therapy whereas 44 patients (47%) died due to aspergillosis. Multivariate analysis showed that corticosteroid therapy [hazard ratio (HR) 10.65; 95% confidence interval (CI) 1.03-110.15, p = 0.047] and pulmonary infection [HR 18.06; 95% CI 4.28-76.17, p < 0.001] were significant predictive factors of death. Conclusions: Epidemiology and outcomes of IA among Thai patients were comparable to those in Western countries. Early diagnosis of IA in patients at risk is still essentially required in order to offer appropriate therapy, decrease morbidity, and mortality rate.